2002
DOI: 10.1007/bf02708016
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic investigation of the MOCVD of copper films frombis(2,2,6,6-tetramethyl-3,5-heptadionato)copper(II)

Abstract: Equilibrium concentrations of various condensed and gaseous phases have been thermodynamically calculated, using the free energy minimization criterion, for the metalorganic chemical vapour deposition (MOCVD) of copper films using bis(2,2,6,6-tetramethyl-3,5-heptadionato)copper(II) as the precursor material. From among the many chemical species that may possibly result from the CVD process, only those expected on the basis of mass spectrometric analysis and chemical reasoning to be present at equilibrium, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…By comparison, the activation energy for metal organic chemical vapor deposition (MOCVD) using copper(II) hexafluoroacetylacetone, Cu(hfac) 2 , has been reported to be ∼75−80 kJ/mol. , In those studies, the surface reaction was assumed to be the rate-limiting step. The activation energy calculated from data reported for MOCVD using bis(2,2,6,6-tetramethyl-3,5-heptadionato)copper(II), Cu(tmhd) 2 , was ∼60 kJ/mol . Son et al reported an activation energy of 62.8 kJ/mol for copper deposition from hexafluoroacetylacetonatecopper(I) allyltrimethylsilane, (hfac)Cu(ATMS), in a reaction rate-limited regime .…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, the activation energy for metal organic chemical vapor deposition (MOCVD) using copper(II) hexafluoroacetylacetone, Cu(hfac) 2 , has been reported to be ∼75−80 kJ/mol. , In those studies, the surface reaction was assumed to be the rate-limiting step. The activation energy calculated from data reported for MOCVD using bis(2,2,6,6-tetramethyl-3,5-heptadionato)copper(II), Cu(tmhd) 2 , was ∼60 kJ/mol . Son et al reported an activation energy of 62.8 kJ/mol for copper deposition from hexafluoroacetylacetonatecopper(I) allyltrimethylsilane, (hfac)Cu(ATMS), in a reaction rate-limited regime .…”
Section: Resultsmentioning
confidence: 99%
“…The heaviest masses and most prominent peaks were formed from the loss of t -butyl groups from each ligand (Figure a). As shown previously in studies of this compound using either photons or electrons as the ionization source, the loss of a t -butyl group from a TMHD ligand is an important step to reaching the formation of neutral copper. As a t -butyl group dissociates, a hydrogen atom from the dissociated t -butyl takes its place. This mechanism has been reported using electroionization mass spectrometry .…”
Section: Resultsmentioning
confidence: 74%
“…using either photons or electrons as the ionization source, the loss of a t-butyl group from a TMHD ligand is an important step to reaching the formation of neutral copper. [41][42][43][44] As a t-butyl group dissociates, a hydrogen atom from the dissociated t-butyl takes its place. This mechanism has been reported using electroionization mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen reduction route requires the attainment of a considerable nominal thickness before coalescence occurs, and consequently, values of the electrical resistivity are mostly provided for thicknesses exceeding 100 nm, 13,16,[21][22][23][24][25][26][27][28] as presented in Fig. 4b.…”
Section: Resultsmentioning
confidence: 99%